A high level of TGF-B1 promotes endometriosis development via cell migration, adhesiveness, colonization, and invasiveness†. Issue 4 (13th November 2018) - Soni, Upendra Kumar; Chadchan, Sangappa Basanna; Kumar, Vijay; Ubba, Vaibhave; Khan, Mohammad Tariq Ali; Vinod, Budai Shanmukha Vivek; Konwar, Rituraj; Bora, Himangsu Kousik; Rath, Srikanta Kumar; Sharma, Sharad; Jha, Rajesh Kumar
Abstract: Endometriosis is a prevalent gynecological disorder that eventually gives rise to painful invasive lesions. Increased levels of transforming growth factor-beta 1 (TGF-B1) have been reported in endometriosis. However, details of the effects of high TGF-B1 on downstream signaling in ectopic endometrial tissue remain obscure. We induced endometriotic lesions in mice by surgical auto-transplantation of endometrial tissues to the peritoneal regions. We then treated endometriotic (ectopic and eutopic endometrial tissues) and nonendometriotic (only eutopic endometrial tissues) animal groups with either active TGF-B1 or PBS. Our results demonstrate that externally supplemented TGF-B1 increases the growth of ectopically implanted endometrial tissues in mice, possibly via SMAD2/3 activation and PTEN suppression. Adhesion molecules integrins (beta3 and beta8) and FAK were upregulated in the ectopic endometrial tissue when TGF-B1 was administered. Phosphorylated E-cadherin, N-cadherin, and vimentin were enhanced in the ectopic endometrial tissue in the presence of TGF-B1 in the mouse model, and correlated with epithelial-mesenchymal transition (EMT) in ovarian endometriotic cells of human origin. Furthermore, in response to TGF-B1, the expression of RHOGTPases (RAC1, RHOC, and RHOG) was increased in the human endometriotic cells (ovarian cyst derived cells from endometriosis patient) and tissues from the mouse model of endometriosis (ectopic endometrial tissue). TGF-B1 enhanced the migratory, invasive, and colonizing potential of human endometriotic cells. Therefore, we conclude that TGF-B1 potentiates the adhesion of ectopic endometrial cells/tissues in the peritoneal region by enhancing the integrin and FAK signaling axis, and also migration via cadherin-mediated EMT and RHOGTPase signaling cascades. Abstract : TGF-B1 regulates the pathophysiology of endometriosis by specifically enhancing the migration, attachment, proliferation, colonization, and invasiveness of floating endometriotic cells or tissues, via the integrin-FAK, cadherin, and RHOGTPase signaling cascades.